Father to son : becoming a man of honor - Oster, Merrill J., 1940- (San Bernardino, CA : Here's Life Publishers, 1988)
A father advises his son, a young man coming of age, on spiritual and social issues in such areas as relationships, goals, inner life, and preparedness.
Bibliography: p. [137]-[138]
Keywords: Young men -- Religious life; Young men -- Conduct of life; Christian life; Conduct of life